Dampak Kinerja Sukuk terhadap Pertumbuhan Ekonomi di Negara Islam ASEAN - Ro’is, Muhammad; Wahab, Abdul Aziz; Fajri, Ahmad (Economic Reviews Journal, 2024)
The ASEAN region has an important role in the global economy, this is of particular interest to examine how economic conditions in ASEAN countries. This study aims to determine the effect of sukuk on economic growth as represented by the GDP variable. The population in this study used three ASEAN countries that have the largest Muslim population, namely, Indonesia, Malaysia and Brunei Darussalam. Using secondary data obtained from the official government website of each country, with data frequency starting from Q1 2015 to Q4 2022, so that the total data obtained is 32. The data is processed using regression tests with the help of SPSS software version 25. The results showed that sukuk had a positive effect on the economies of Indonesia and Malaysia and had no effect on the economy of Brunei Darussalam.